A missing magnetic energy paradox - Grosse, Constantino (2013)
While the interaction forces between two electric and two magnetic dipoles are formally identical, their interaction energies differ because in addition to mechanical work, the magnetic energy includes the electrical work needed to keep the dipole moments unaltered. This energy difference appears to contradict a calculation based on the integrals of the squares of the electric and magnetic fields since the electric and magnetic dipole fields have precisely the same geometry.